Usability Testing Pada APPFIN Menggunakan Metode System Usability Scale Studi Kasus PT. Maja Kerta Wang - Budiman Budiman; Rd. Yadi Rakhman Alamsyah; Ahmad Fauzi Ramadhan (NUANSA INFORMATIKA, 2024)
Ensuring a positive user experience is essential for the success of usability testing and meeting user expectations in system development. In this study, the System Usability Scale method is employed for usability testing, utilizing a questionnaire to assess acceptance, grading, and ratings. The research involves end users of the APPFIN application across all branches and head offices, with twenty-nine respondents achieving a notably favorable acceptance rate. The System Usability Scale score of 82 places APPFIN in the "GOOD" category with a B grade, indicating a reasonably high level of user satisfaction. The majority of respondents expressed contentment with their experience using APPFIN, reflecting a positive reception and acceptance among users.